(untitled) (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2024)
The automotive industry is not only concerned with vehicle sales, but also after-sales services such as providing official workshops for vehicle maintenance. This condition causes intense competition among official repair shop managers, which allows customer loyalty to become lower. The aim of this research is to determine the influence of service quality and price perception on customer loyalty, mediated by customer satisfaction. This research was conducted at the Suzuki Indo Permai Veteran Denpasar Workshop. The population of this study was 1,912 customers recorded in 2023. The sample was determined using the Slovin formula so that the sample size was determined to be 95 customers using accidental sampling. The analysis technique used is path analysis with the help of SPSS software. The results of the analysis prove that customer satisfaction mediates the influence of service quality and price perception on customer loyalty. Suggestions given include improving the comfort of the waiting room, holding sales promotions, and educating customers about the authenticity of spare parts.